The Construction of the Anthropology of Communication: Towards a Theoretical and Methodological Proposal - Herrera Aguilar, Miriam (CIENCIA ergo-sum; Vol. 22 Núm. 2 (2015): CIENCIA ergo-sum (julio-octubre 2015), 2015)
This paper assumes that communication sciences examine the communication itself in a large and interdisciplinary way. In this sense, during several decades, researchers have been projecting the Anthropology of Communication like a theoretical and methodological proposal for the academic work in Communication. The objective here is to set the relevance of keeping up this proposal: it tries, as a theory, to understand the communication world in its anthropological dimension and, at the same time, as a method, to offer elements to investigate from a qualitative perspective. In conclusion, since this project nowadays involves the interest and contributions of researchers from different latitudes, its relevance and the possibility of keeping it up are supported in this work.